Designing a primary care pharmacist-led review for people treated with opioids for persistent pain: a multi-method qualitative study - Charlotte Woodcock; Nicola Cornwall; Lisa Dikomitis; Sarah A Harrisson; Simon White; Toby Helliwell; Roger Knaggs; Eleanor Hodgson; Tamar Pincus; Miriam Santer; Christian D Mallen; Julie Ashworth; et al. (BJGP Open, 2024)
Background: Opioids are frequently prescribed for persistent non-cancer pain despite limited evidence of long-term effectiveness and risk of harm. Evidence-based interventions to address inappropriate opioid prescribing are lacking. Aim: To explore perspectives of people living with persistent pain to understand barriers and facilitators in reducing opioids in the context of a pharmacist-led primary care review, and identify review components and features for optimal delivery. Design & setting: A multi-method qualitative study undertaken in the primary care setting in the UK. Method: Adults with experience of persistent pain and taking opioids participated in semi-structured interviews (n = 15, 73% female) and an online discussion forum (n = 31). The Theoretical Domains Framework (TDF) provided a framework for data collection and thematic analysis, involving deductive analysis to TDF domains, inductive analysis within domains to generate sub-themes, and sub-theme comparison to form across-domain overarching themes. The behaviour change technique taxonomy (v1) and motivational behaviour change technique classification system were used to systematically map themes to behaviour change techniques to identify potential review components and delivery features. Results: Thirty-two facilitator and barrier sub-themes for patients reducing opioids were identified across 13 TDF domains. These combined into the following six overarching themes: learning to live with pain; opioid reduction expectations; assuming a medical model; pharmacist-delivered reviews; pharmacist–patient relationship; and patient engagement. Sub-themes mapped to 21 unique behaviour change techniques, yielding 17 components and five delivery features for the proposed PROMPPT review. Conclusion: This study generated theoretically informed evidence for design of a practice pharmacist-led PROMPPT review. Future research will test the feasibility and acceptability of the PROMPPT review and pharmacist training.